School milk initiative: Impact of adding milk to a micronutrient fortified school feeding program: An effectiveness trial in humanitarian settings - Bliznashka, Lilia (International Food Policy Research Institute, 2024)
Presentation given July 30, 2024 for CGIAR Research Initiative on Fragility, Conflict, and Migration given on behalf of Aulo Gelli, Dalia El Sabbagh, Monica George Michail, and the School Milk Initiative Trial Group.